The elephant in the room: The role of failed invasions in understanding invasion biology. - Zenni, Rafael D. (2012)
Most species introductions are not expected to result in invasion, and species that are invasive in one area are frequently not invasive in others. However, cases of introduced organisms that failed to invade are reported in many instances as anecdotes or are simply ignored. In this analysis, we aimed to find common characteristics between non-invasive populations of known invasive species and evaluated how the study of failed invasions can contribute to research on biological invasions. We found intraspecific variation in invasion success and several recurring explanations for why non-native species fail to invade; these included low propagule pressure, abiotic resistance, biotic resistance, genetic constraints and mutualist release. Furthermore, we identified key research topics where ignoring failed invasions could produce misleading results; these include studies on historical factors associated with invasions, distribution models of invasive species, the effect of species traits on invasiveness, genetic effects, biotic resistance and habitat invasibility. In conclusion, we found failed invasions can provide fundamental information on the relative importance of factors determining invasions and might be a key component of several research topics. Therefore, our analysis suggests that more specific and detailed studies on invasion failures are necessary.